Effect of Y2O3 on the oxidation properties of ZrSi2/SiC coating prepared by SAPS on the carbon-carbon composites. Issue 13 (September 2018) - Liu, Fei; Li, Hejun; Gu, Shengyue; Yao, Xiyuan; Fu, Qiangang
Abstract: In order to improve the oxidation resistance of carbon-carbon (C/C) composites at high temperature, different content of Y2 O3 modified ZrSi2 /SiC coating for C/C composites were prepared by pack cementation and supersonic atmosphere plasma spraying (SAPS). Microstructure observation and phase identification of the coatings were analyzed by SEM, XRD, DSC/TG and EDS. Experimental results shown that the coating with 10 wt% Y2 O3 effectively protected C/C composites from oxidation at 1500 °C in air for 301 h with a mass loss of 0.13% and experienced 18 thermal shock times from room temperature (RT) to 1500 °C. First, Y2 O3 could restrain the phase transition of ZrO2 to reduce the formation of thermal stresses of the coating; second, the random distribution of ZrO2 ceramic particles and the formation of ZrSiO4 enhanced the stability of the SiO2 ; third, the formation of Y2 Si2 O7 and Y2 SiO5 could relieve the thermal mismatch between ZrSi2 -Y2 O3 outer layer and the inner layer.